O turismo de base local como um possível indutor de desenvolvimento rural: uma análise da realidade e das potencialidades no Distrito de Dondo-Moçambique - Chicico, Felicidade da Juliana (2012)
The current debate on rural development focuses on the territorial approach, recognizing the multifunctional character of rural areas. Emphasize the use of endogenous forces, the need of implement policies which valorize local specificities, the participation of social actors in revitalization of rural areas. In this context tourism enters as a means to induce a new dynamic to rural areas, since the activity is regarded as a channel for the upgrading of the natural and cultural resources and the rural way of life. This study focuses on local-based tourism as a promoter of rural development, giving an analysis of the social reality and potential for this tourism in the district of Dondo. In it, is proposed to analyze the potential for development of local-based tourism in the district of Dondo, assessing the extent to which local reality enables the inclusion of the community in the management of local tourism resources. For this, was showed the inclusion of local-based tourism in the current context of rural development, was identified and organized systematically the factors that influence the implementation of local-based tourism in the study area and was verified as far as possible the study area corresponds to the constraints identified, showing how local-based tourism can best been encouraged. Was adopted a qualitative methodological approach to both the procedures and data processing, but also by critical approach, using bibliographical research, semi-structured interviews that fell on the group of public administrators who work in tourism and community leaders. The critical analysis was based on the principles of sustainability o Sachs particular ecological, social, cultural, economic, space, beyond the analysis of political and institutional aspects. The survey results show that the district of Dondo has a potential for implementing a model of tourism development on a local basis, since it is rich in natural and cultural research, benefits from good network accessibility in the context of the market in the region, the population live according to their habits and customs and value their identity. There is also a good cooperation between community members, although not in tourism, a fact which is observed through the lever of community participation in associations, cooperatives, working in areas such as agriculture, fishing, environment, civic education etc. It also has public funding sources to augment or stimulate local investment. Despite obstacles such as inexistence of policies and local plans for tourism development, lack of awareness of tourism, lack of basic infrastructure, as well as equipment and facilities to support tourism, the results shows that these problems can be solved through a public commitment from both government, and community through a joint planning and participation